Attachment in retailing sector: Retailer own-brands or manufacturer brands? - Loureiro, S. M. C. (9th Annual Conference of the EuroMed Academy of Business: Innovation, Entrepreneurship and Digital Ecosystems, 2016)
The aims of this study are (i) to explore the effect of brand credibility, familiarity and brand image on brand attachment and brand attitude; and (ii) to test how a grocery product category and the perception of quality of own-label brands versus manufacturer brands moderate the inter-relationship of brand credibility, brand familiarity and brand image on brand attachment and brand attitude. A survey is administered to a quota sample of Portuguese supermarket shoppers via a face-to-face personal interviewing method. Findings reveal that all relationships are significant except brand familiarity on brand attitude. Credibility and familiarity seem to be more important to enhance attachment in the case of the manufacturer brands and image in the case of retailer own-brands.